On Pre-Commutative Algebras - Hee Sik Kim; Joseph Neggers; Sun Shin Ahn (Mathematics, 2019)
In this paper, we introduce the notions of generalized commutative laws in algebras, and investigate their relations by using Smarandache disjointness. Moreover, we show that every pre-commutative <semantics> B C K </semantics> -algebra is bounded.